2021
DOI: 10.4103/jpbs.jpbs_740_20
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Perception, and Attitude on Conservative and Endodontic Practice on COVID Pandemic Situation: A Qualitative Research

Abstract: Aim: The purpose of our study was to analyze the knowledge and attitude of conservative as well as endodontic practice among dental professionals during coronavirus pandemic situation. Methodology: A cross-sectional study was conducted over a period of 3 months among 1256 dental surgeons, which included 400 MDS and 856 BDS dentists. Questionnaire assessed knowledge of the participants about COVID-19, risk assessment about the pandemic, preparedness of the participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…The current study demonstrated the process of developing a new instrument to evaluate the adherence of dental practitioners to the guidelines provided by the DCI. Previous studies analyzed the knowledge, preparedness, and attitude of dental clinicians towards the COVID-19 pandemic; however, to the best of the authors’ knowledge, a survey tool to measure the uptake of the recommended guidelines (instituted during the COVID-19 pandemic) by dental clinicians is currently lacking [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study demonstrated the process of developing a new instrument to evaluate the adherence of dental practitioners to the guidelines provided by the DCI. Previous studies analyzed the knowledge, preparedness, and attitude of dental clinicians towards the COVID-19 pandemic; however, to the best of the authors’ knowledge, a survey tool to measure the uptake of the recommended guidelines (instituted during the COVID-19 pandemic) by dental clinicians is currently lacking [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Menhadji et al, 2021) Temuan ini sejalan dengan studi oleh Khatore et al yang menunjukkan hanya 12% subjek yang percaya bahwa konsultasi jarak jauh dapat menjadi alternatif kunjungan konvensional untuk prosedur elektif di bidang konservasi dan endodontik. (Khatore et al, 2021)…”
Section: B Sikap Terhadap Teledentistryunclassified
“…Pengumpulan data dalam 14 studi hanya menggunakan kuesioner, sedangkan 1 studi menggunakan kuesioner dan wawancara. Sebanyak 4 studi berasal dari Arab Saudi (Aboalshamat, 2020;Al Mohaya et al, 2021;Almulhim et al, 2021;Nassani et al, 2021), 2 studi dari Pakistan (Abbas et al, 2020;Subhan et al, 2021), 2 studi dari India (George et al, 2021;Khatore et al, 2021), serta masing-masing 1 studi berasal dari Amerika (Tiwari et al, 2022), Kolombia(Plaza-Ruíz et al, 2021), Brazil(Raucci-Neto et al, 2022, Indonesia (Soegyanto et al, 2022), Inggris (Menhadji et al, 2021), dan Italia. (Sinjari et al, 2020) Terdapat 1 studi yang mengumpulkan responden dari berbagai negara di Asia, Eropa dan Amerika.…”
unclassified
See 1 more Smart Citation